Does moderate alcohol consumption affect fertility? Follow up study among couples planning first pregnancy. Issue 7157 (22nd August 1998) - Jensen, Tina Kold; Hjollund, Niels Henrik I; Henriksen, Tine Brink; Scheike, Thomas; Kolstad, Henrik; Giwercman, Aleksander; Ernst, Erik; Bonde, Jens Peter; Skakkebæk, Niels E; Olsen, J⊘rn
Abstract: Objective : To examine the effect of alcohol consumption on the probability of conception. Design : A follow up study over six menstrual cycles or until a clinically recognised pregnancy occurred after discontinuation of contraception. Subjects : 430 Danish couples aged 20-35 years trying to conceive for the first time. Main outcome measures : Clinically recognised pregnancy. Fecundability odds ratio: odds of conception among exposed couples divided by odds among those not exposed. Results : In the six cycles of follow up 64% (179) of women with a weekly alcohol intake of less than five drinks and 55% (75) of women with a higher intake conceived. After adjustment for cycle number, smoking in either partner or smoking exposure in utero, centre of enrolment, diseases in female reproductive organs, woman's body mass index, sperm concentration, and duration of menstrual cycle, the odds ratio decreased with increasing alcohol intake from 0.61 (95% confidence interval 0.40 to 0.93) among women consuming 1-5 drinks a week to 0.34 (0.22 to 0.52) among women consuming more than 10 drinks a week (P=0.03 for trend) compared with women with no alcohol intake. Among men no dose-response association was found after control for confounders including women's alcohol intake. Conclusion : A woman's alcohol intake is associated with decreased fecundability even among women with a weekly alcohol intake corresponding to five or fewer drinks. This finding needs further corroboration, but it seems reasonable to encourage women to avoid intake of alcohol when they are trying to become pregnant.